Pengaruh Pertumbuhan Ekonomi dan Inflasi Pada Penerimaan PPN (Studi Kasus Pada Kantor Pelayanan Pajak Se-Bali) - Puspitha, Putu Vilia; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2018)
Value Added Taxis one of the second largest tax revenue of the tax system. This studyaims to determineand test empirically the influenceof economic growth and inflation to the revenue valueaddedtax. ThisresearchwasconductedatTaxOffice of Bali during the period 2012-2016. The number of samples under study 8 Tax Office. The methodofdetermining thesample using non probability sampling method withsaturatedsampling technique, that is the entire population is sampled. Data collectionwas donethrough documentation. The analysistechniqueused is multiple linear regression analysis. Basedontheresultsof theanalysis,concludedthat economic growth has apositive effectonvalue added tax revenue. Inflation has no effect on the revenue of value addedtax. Keyword: Economic growth, inflation, value added tax.